Consumers' Social Media Brand Behaviors: Uncovering Underlying Motivators and Deriving Meaningful Consumer Segments. Issue 5 (May 2017) - Dimitriu, Radu; Guesalaga, Rodrigo
ABSTRACT: The current research identifies the range of social media brand behaviors (i.e., brand touch points) that consumers can exhibit on social media, and subsequently queries a representative sample of consumers with regard to such behaviors. The analysis reveals four underlying motivators for consumers' social media behaviors, including brand tacit engagement, brand exhibiting, brand patronizing, and brand deal seeking. These motivators are used to derive meaningful consumer segments identified as content seekers, observers, deal hunters, hard‐core fans, posers and, respectively, patronizers, and described through co‐variates including brand loyalty, brand attachment, and social media usage. The findings are critically discussed in the light of literature on the needs that consumers meet through brand consumption and on the types of relationships consumers build with brands. Not least, the managerial implications of the current findings are debated.